Cps1-Compliant Regulation Using a Psd Analysis of Wind Expansion in a Single Balancing Authority - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2015)
The integration of wind power has imposed new requirements for regulation reserves. For ensuring adequate regulation reserves, wind power variability and uncertainty must be estimated, and system frequency must comply with frequency performance standards. This work determines regulation capacity and ramping capability requirements as a function of wind-installed capacity to comply with CPS1, the North American Electric Reliability Corporation (NERC) Control Performance Standard 1 for the case of a single balancing authority. A simulation of the Electric Reliability Council of Texas (ERCOT) will be presented to examine the performance of the formulation. © 2010-2012 IEEE.